Spásbháid, spásárthaí and spáslonga: Issues of Terminology in the Translation of Sci‑fi and Fantasy into Irish - Mark Ó Fionnáin (Ksiegarnia Akademicka Publishing, 2017)
This article looks at the issue of terminology in Irish language translations of science fiction and fantasy. Although there are no original works per se in the language, there do exist several translations of well‑known international works. This has given rise to the problem of what to do in those cases where concepts or terms do not exist, or have never existed, in Irish: should a term be coined or invented, should they be left in the original form, or should they be written according to Irish orthographic rules? This article examines the reaction to the Irish translation of The Hobbit and of the main terms therein, and then focuses on those cases where Irish does have terms, but which are not one‑to‑one equivalents for the English word in question.